The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2024
DOI: 10.3390/biomimetics9030174
|View full text |Cite
|
Sign up to set email alerts
|

Size Control of Biomimetic Curved-Edge Vaterite with Chiral Toroid Morphology via Sonochemical Synthesis

Ki Min,
Dong Kim,
Seung Pack

Abstract: The metastable vaterite polymorph of calcium carbonate (CaCO3) holds significant practical importance, particularly in regenerative medicine, drug delivery, and various personal care products. Controlling the size and morphology of vaterite particles is crucial for biomedical applications. This study explored the synergistic effect of ultrasonic (US) irradiation and acidic amino acids on CaCO3 synthesis, specifically the size, dispersity, and crystallographic phase of curved-edge vaterite with chiral toroids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The presence of Lys enhanced the yield of CaCO 3 and controlled the morphology and crystal phase of the CaCO 3 . A further study on the control of the calcium carbonate structure using amino acids demonstrated the efficacy of sound waves (ultrasonic irradiation) and L- or D-aspartic acid in the creation of small, uniquely shaped calcium carbonate particles, which are more suitable for medical applications such as drug delivery and bone healing [ 243 ]. Gene therapy is an important treatment for complex diseases, and inorganic CaCO3 nanoparticles have been utilized for efficient gene delivery.…”
Section: Biominerals and Composite Materials In Regenerative Medicinementioning
confidence: 99%
“…The presence of Lys enhanced the yield of CaCO 3 and controlled the morphology and crystal phase of the CaCO 3 . A further study on the control of the calcium carbonate structure using amino acids demonstrated the efficacy of sound waves (ultrasonic irradiation) and L- or D-aspartic acid in the creation of small, uniquely shaped calcium carbonate particles, which are more suitable for medical applications such as drug delivery and bone healing [ 243 ]. Gene therapy is an important treatment for complex diseases, and inorganic CaCO3 nanoparticles have been utilized for efficient gene delivery.…”
Section: Biominerals and Composite Materials In Regenerative Medicinementioning
confidence: 99%